Permanent and Transitory Movements in Labor Income: An Explanation for "Excess Smoothness" in Consumption - Quah, Danny (Journal of Political Economy, 1990)
Many have argued that if labor income is difference stationary, the permanent income hypothesis predicts that consumption should be relatively volatile. In U.S. aggregate data, labor income is well characterized as having a unit root; however, consumption turns out to be relatively smooth. This anomaly is known as Deaton's paradox. I resolve Deaton's paradox by providing decompositions of labor income into permanent and transitory components. These preserve the univariate dynamic properties of labor income. However, when agents distinguish permanent and transitory movements in their labor income–as the rational expectations hypothesis asserts they should–the permanent income hypothesis correctly predicts the observed smoothness in consumption.